Pengaruh Electronic Word of Mouth, Perceived Quality, dan Brand Image terhadap Minat Beli pada Produk Somethinc - Shela Irvara Wulandari; Mochammad Isa Anshori (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of electronic word of mouth (e-WOM), perceived quality, and brand image on purchase intention of Somethinc products. The approach used is quantitative method, with a population consisting of students of the Faculty of Economics and Business, Trunojoyo University Madura who have seen reviews about Somethinc products and have interest or experience in using them. A total of 100 respondents were involved in this study, which was determined through purposive sampling technique. Data analysis was conducted using multiple linear regression. The findings show that e-WOM and perceived quality have a positive and significant effect on purchase intention, while brand image does not show a significant effect on consumer purchase intention.